gronomic and nutritional evaluation of genotypes of Chloris gayana for the Colombian livestock - Mejía-Salazar, Julián Roberto (2021)
Introduction. Grazing forages are the main feed source for livestock. Climatic variation challenges producers to maintain a constant supply of food, so it is necessary to explore other forage alternatives. Objective. To evaluate the performance of twenty genotypes of Chloris gayana for livestock farms. Materials and methods. The work was carried out at the El Nus Research Center of the Corporacion Colombiana de Investigacion Agropecuaria (AGROSAVIA), San José del Nus, Antioquia, Colombia. A randomized complete block design, three repetitions, and twenty treatments (Chloris gayana genotypes) was used. The analysis used a mixed model repeated measures over time, with the GLIMMIX procedure, whose time effect was represented by cut-off age. The cutting frequencies used were 21, 28, 35, and 42 days, between August 2017 and October 2019 in low and high rainfall seasons. Vigor, species cover, plant height, pests, and pathogen incidence, flowering, dry matter yield (MS), crude protein (PC), fiber in neutral and acid detergent (FDN, FDA), lignin (LIG), digestibility (DIG), hemicellulose (HEM), and net lactation energy (ENL) were evaluated. Results. The characters that contributed the greatest variability corresponded to MS, PC, FDN, FDA, and DIG; an association was observed between DIG, HEM, and ENL. There were differences between seasons and between genotypes for most of the variables, except for PC. Lignin was the only variable that showed a difference in the triple interaction (genotype*season*cutting days). The genotype*season interaction showed differences for FDA and LIG. Genotype 13103 obtained the highest MS yield (3032.2 kg DM ha-1). B. decumbens had the lowest content of FDA and LIG; but the highest of digestibility. Conclusions. The experimental genotypes presented similar or even better productivity and nutritional characteristics than the controls.